Silencing of Long Non-coding RNA MIAT Sensitizes Lung Cancer Cells to Gefitinib by Epigenetically Regulating miR-34a - Fu, Yunfeng; Li, Chengyuan; Luo, Yanwei; Li, Lian; Liu, Jing; Gui, Rong (Frontiers in Pharmacology, 2018)
Long non-coding RNA (lncRNA) myocardial infarction associated transcript (MIAT) was recently identified as oncogene in several cancers. However, the role of MIAT on acquired resistance in lung cancer and the underlying mechanisms remain unclear. Here, we showed that the expression of MIAT in lung cancer tissues was upregulated compared with adjacent tissues. LncRNA MIAT expression was associated with tumor size, lymph node metastasis, distant metastasis and TNM stage. Univariate analysis and multivariate analysis revealed that the lncRNA MIAT to be an independent factor for predicating the prognosis of lung cancer patients. Low lncRNA MIAT have longer overall survival time and progression-free survival time than patients with high lncRNA MIAT expression. Moreover, the knockdown of MIAT significantly sensitized PC9 and gefitinib-resistant PC9 cells to gefitinib in vitro and in vivo, and increased the expression of miR-34a and inactivated PI3K/Akt signaling. MIAT interacted with miR-34a and epigenetically controlled the miR-34a expression by hyper-methylating its promotor. Taken together, our findings demonstrated that knockdown of MIAT by siRNA enhances lung cancer cells to gefitinib through the PI3K/Akt signaling pathway by epigenetically regulating miR-34a. Thus, MIAT may be a useful prognostic marker and therapeutic target for lung cancer patients.